Non-Noble Plasmonic Metal-Based Photocatalysts - Sayed, Mahmoud; Yu, Jiaguo; Liu, Gang; Jaroniec, Mietek (Chemical reviews, 2022)
Solar-to-chemical energy conversion via heterogeneous photocatalysis is one of the sustainable approaches to tackle the growing environmental and energy challenges. Among various promising photocatalytic materials, plasmonic-driven photocatalysts feature prominent solar-driven surface plasmon resonance (SPR). Non-noble plasmonic metals (NNPMs)-based photocatalysts have been identified as a unique alternative to noble metal-based ones due to their advantages like earth-abundance, cost-effectiveness, and large-scale application capability. This review comprehensively summarizes the most recent advances in the synthesis, characterization, and properties of NNPMs-based photocatalysts. After introducing the fundamental principles of SPR, the attributes and functionalities of NNPMs in governing surface/interfacial photocatalytic processes are presented. Next, the utilization of NNPMs-based photocatalytic materials for the removal of pollutants, water splitting, CO2 reduction, and organic transformations is discussed. The review concludes with current challenges and perspectives in advancing the NNPMs-based photocatalysts, which are timely and important to plasmon-based photocatalysis, a truly interdisciplinary field across materials science, chemistry, and physics.